Regulation of Glutamate, GABA and Dopamine Transporter Uptake, Surface Mobility and Expression - Ryan, Renae M.; Ingram, Susan L.; Scimemi, Annalisa (Frontiers in Cellular Neuroscience, 2021)
Neurotransmitter transporters limit spillover between synapses and maintain the extracellular neurotransmitter concentration at low nanomolar levels. They also exert a key role in providing precursors for neurotransmitter biosynthesis. In many cases, neurons and astrocytes contain a large intracellular pool of transporters that can be redistributed and stabilized in the plasma membrane following activation of different signaling pathways. This means that the uptake capacity of the brain neuropil for different neurotransmitters can be dynamically regulated over the course of minutes, as an indirect consequence of changes in neuronal activity, blood flow, cell-to-cell interactions, etc. Here we discuss recent advances in the mechanisms that control the cell membrane trafficking and biophysical properties of transporters for the excitatory, inhibitory and modulatory neurotransmitters glutamate, GABA and dopamine.